Analysis of factors affecting enoxaparin effectiveness on coagulation, inflammation, and clinical outcomes in patients with COVID-19 - Budi Suprapti; Liana Debora; Rifdah Atikah Safitri; Dewi Kusumawati; Arina Dery Puspitasari (GarVal Editorial Ltda., 2023)
Context: Hypercoagulopathy is a COVID-19 extra-pulmonary manifestation has drawn the attention of the scientists due to its risk of thromboembolism. Enoxaparin is an anticoagulant used to prevent hypercoagulopathy. Many factors have been associated with enoxaparin effectiveness. Aims: To analyze factors affecting enoxaparin effectiveness on coagulation, inflammation, and clinical outcomes. Methods: This retrospective cohort study involved hospitalized adult patients with COVID-19 from November 2020 to April 2021. Patients' age, gender, body mass index (BMI), comorbidity, and laboratory results were extracted from medical records. Factors influencing enoxaparin efficacy on coagulation, inflammation, and clinical outcomes were analyzed using path analysis with SmartPLS 3.0 software. D-dimer and platelet values was determined as coagulation outcomes and C-reactive protein (CRP) value as an inflammation outcome. Clinical outcomes comprised of mortality, ventilator usage, and length of stay. Results: A total of 269 patients fulfilled the inclusion criteria. Most of the subjects were male (58%), 66% had comorbidities, 48.3% were aged ≥60 years old, and 65.8% had a BMI ≥ 25 kg/m2. Path analysis showed that age, BMI, and comorbidity affected disease severity (p<0.05). Disease severity strongly influenced enoxaparin dosage (p=0.000). Dosage affected platelet value, ventilator usage, and mortality (p<0.05). Gender did not influence disease severity, and dosage displayed no significant effect on length of stay, CRP, and D-dimer (p>0.05). Conclusions: Dosage is the main factor influencing enoxaparin efficacy on coagulation, inflammation, and clinical outcomes. The dosage is strongly affected by disease severity, in which is predominantly influenced by age, BMI, and comorbidity.